Inter-annual sea level change and transgression along a barrier Island coast - Zarillo, Gary A. (Frontiers in Environmental Science, 2023)
On the decadal time scale coastal planning and management scale of relative sea rise level is usually considered as a trend or constant rate in rather than a dynamic, time varying influence on coastal change. However, Coastal ocean sea level of along the east Florida coast and coastal regions further north is, to a first order, is controlled at the interannual and decadal time scale by the dynamics of North Atlantic circulation and Gulf Stream flow and described by Ezer et al., 2013. However, every coastal region has its own 'fingerprint" annual sea level cycle, as well as longer-term, intra- and inter-decadal sea-level oscillations. This paper addresses the influence of the strong Florida coastal ocean sea level signal on topographic evolution of the shoreface, coastal sediment budgets, and potential for coastal transgression at the decadal time scale.